Quantitative analysis of γ–oryzanol content in cold pressed rice bran oil by TLC–image analysis method - Apirak Sakunpak; Jirapornchai Suksaeree; Chaowalit Monton; Pathamaporn Pathompak; Krisana Kraisintu (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To develop and validate an image analysis method for quantitative analysis of γ-oryzanol in cold pressed rice bran oil. Methods: TLC-densitometric and TLC-image analysis methods were developed, validated, and used for quantitative analysis of γ-oryzanol in cold pressed rice bran oil. The results obtained by these two different quantification methods were compared by paired t-test. Results: Both assays provided good linearity, accuracy, reproducibility and selectivity for determination of γ-oryzanol. Conclusions: The TLC-densitometric and TLC-image analysis methods provided a similar reproducibility, accuracy and selectivity for the quantitative determination of γ-oryzanol in cold pressed rice bran oil. A statistical comparison of the quantitative determinations of γ-oryzanol in samples did not show any statistically significant difference between TLC-densitometric and TLC-image analysis methods. As both methods were found to be equal, they therefore can be used for the determination of γ-oryzanol in cold pressed rice bran oil.